Characteristic dislocation substructure in 101¯2 twins in hexagonal metals. (15th January 2018) - Wang, F.; Hazeli, K.; Molodov, K.D.; Barrett, C.D.; Al-Samman, T.; Molodov, D.A.; Kontsos, A.; Ramesh, K.T.; El Kadiri, H.; Agnew, S.R.
Abstract: Based on transmission electron microscopy results from pure Mg single crystal examined in the current work, and Mg alloys and other hexagonal metals in literature, a characteristic dislocation substructure inside 10 1 ¯ 2 twins is identified. Abundant non-basal [ c ] and ⟨ c + a ⟩ perfect dislocations, as well as basal I 1 stacking faults with widths on the order of 100 nm distributed preferentially in the vicinity of a twin boundary, with a low density zone in the middle of the twin. Considering the ubiquity of 10 1 ¯ 2 twins, this characteristic dislocation substructure should be considered in modeling of hexagonal metal alloy deformation. Graphical abstract: Image 1